Evaluation of a Proposed Biodegradable 188Re Source for Brachytherapy Application. Issue 28 (July 2015) - Khorshidi, Abdollah; Ahmadinejad, Marjan; Hamed Hosseini, S.; Masoomi., Michael
<x xml:space="preserve">Abstract</x> Abstract This study aimed to evaluate dosimetric characteristics based on Monte Carlo (MC) simulations for a proposed beta emitter bioglass 188Re seed for internal radiotherapy applications. The bioactive glass seed has been developed using the sol-gel technique. The simulations were performed for the seed using MC radiation transport code to investigate the dosimetric factors recommended by the AAPM Task Group 60 (TG-60). Dose distributions due to the beta and photon radiation were predicted at different radial distances surrounding the source. The dose rate in water at the reference point was calculated to be 7.43 ± 0.5 cGy/h/μCi. The dosimetric factors consisting of the reference point dose rate, D(r0, θ0), the radial dose function, g(r), the 2-dimensional anisotropy function, F(r, θ), the 1-dimensional anisotropy function, φan(r), and the R90 quantity were estimated and compared with several available beta-emitting sources. The element 188Re incorporated in bioactive glasses produced by the sol-gel technique provides a suitable solution for producing new materials for seed implants applied to brachytherapy applications in prostate and liver cancers treatment. Dose distribution of 188Re seed was greater isotropic than other commercially attainable encapsulated seeds, since it has no end weld to attenuate radiation. The beta radiation-emitting 188Re source provides high doses of local radiation to the tumor tissue and the short range of the beta particles limit damage to the adjacent normal tissue.